Oxidative stress responses following a football game: The effect of playing time - Paschalis, V.; Majuridis, I.; Siomos, T.; Vantarakis, A.; Margonis, K.; Nikolaidis, M.; Kyparos, A.; Taxildaris, K.; Jamurtas, A.; Fatouros, I.; Kouretas, D. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Football is an intermittent, multiple-sprint activity of high intensity performed over an extended period of time. Sudden decelerations and direction changes performed during a football game produces large eccentric forces which are associated with muscle damage (1) and delayed onset of muscle soreness (DOMS) (2). Damaging exercise has been associated with free radical generation and a subsequent inflammation (3). Furthermore, oxygen consumption and mitochondrial oxygen flux increase linked with prolonged intermittent exercise may also increase free radicals generation (4). Free radicals elicit oxidative damage to lipids, proteins, and DNA if antioxidant defenses are overwhelmed (5). Until today, oxidative stress responses following a single football game have not been investigated adequately. The aim of the present study was to investigate whether a football game induces oxidative stress responses in elite football players. Methods Twenty-four elite football players were assigned into 2 groups: a) those who played during the football game (n=14), and b) those who did not play during the game (Control, n=10). Athletes were not engaged in strenuous physical activity for at least 48 hours before and after the game. Blood samples were collected prior to the game, immediately following the game, 24 and 48 hours after the game. Blood samples were analyzed for leukocyte count, creatine kinase (CK), uric acid, serum protein carbonyls (PC), TBARS, catalase, total antioxidant capacity (TAC), and blood glutathione peroxidase (GPX), reduced glutathione (GSH), and oxidized glutathione (GSSG). DOMS, muscle swelling (thigh circumference), knee joint range of motion (KJRM) were also measure at the same time points. Performance (vertical jumping and 1RM in squat) were measured at baseline and 24 and 48 hours after the game. Results None of the variables measured changed in the control group. Catalase and TAC remained unaffected in both groups. Leucocyte count, DOMS, CK, PC, TBARS, GPX, and uric acid were elevated (P<0.05) immediately post-game and remained elevated thereafter. The ratio GSH/GSSG was reduced (P<0.05) at all times following the game in the experimental group. Maximal strength and vertical jumping performance declined (P<0.05) at 24 and 48 hours post-game. A significant (P<0.05) correlation was found between playing time and the ratio GSH/GSSG, C, and leukocyte count. Discussion Our data show that a single football game may increase oxidative stress and muscle damage markers in the circulation. Furthermore, this inflammatory response remained elevated for a prolonged period following the game (48 hours) although athletes were not engaged in any other form of strenuous physical activity or training. This increase in oxidative response following a football game seems to be associated with the athletes` time of participation in the game.